The Essence of Ownership Rights of College Foundation in Social Justice Perspective - A Zulkarnain (Kanun Jurnal Ilmu Hukum, 2021)
This research is based on the essence of the ownership rights of higher education foundations in the perspective of social justice. By looking at several facts related to ownership rights and institutions and their management. This research method is normative with a philosophical approach, laws, theories/concepts, and cases. The data used are secondary data in the form of primary and secondary legal materials. The results show that ownership rights to tertiary institutions are public/community ownership rights that are responsible for trust, not those of the founders, supervisors, administrators, and supervisors. The ownership rights of this foundation are pseudo or imperfect because it is only limited to the right to use or benefit from the existence of the higher education foundation. The ownership rights of the student community over foundations have implications for the management of foundations and universities with the foundation's obligation to provide academic services and economic assistance for underprivileged students.